"Knowledge is Essential for Universal Progress but Fatal to Class Privilege": Working People and The Schools in Vancouver During The 1920s - Barman, Jean (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1988)
Abstract Labour historians have characterized the 1920s as a time of working-class quiescence. The reality, at least in the case of Vancouver, was more complex. The work place may have become quieter, but working people were not inert. Organized activity focussed on the city's schools, not to overturn the system but rather to obtain fairer consideration for the children of working people. By opting for reform over class confrontation, working people allied themselves with like-minded, largely middle-class individuals equally concerned with educational reform. Considerable improvement of facilities resulted, despite active opposition by business interests concerned with immediate economic advantage. The consequence was that more children of working people, and more children generally, stayed in school a little longer.